Controlling a stock pollutant with endogenous investment and asymmetric information - Larry Karp; Jiangfeng Zhang (Fondazione Eni Enrico Mattei (FEEM), 2001)
Non-strategic firms with rational expectations make investment and emissions decisions. The investment rule depends on firms' beliefs about future emissions policies. We compare emissions taxes and quotas when the (strategic) regulator and (nonstrategic) firms have asymmetric information about abatement costs, and all agents use Markov Perfect decision rules. Emissions taxes create a secondary distortion at the investment stage, unless a particular condition holds; emissions quotas do not create a secondary distortion. We solve a linear-quadratic model calibrated to represent the problem of controlling green-house gases. The endogeneity of investment favors taxes, and it increases abatement.
Keywords: C61; D8; H21; Q28; 330; Pollution control; investment; uncertainty; rational expectations; choice of instruments; Investition; Umweltmanagement; Umweltstandard; Ökosteuer; Asymmetrische Information; Rationale Erwartung; Theorie